(untitled) (Economic and Political Thought, 2015)
The vision of “Europe as a club of clubs” constitutes Giandomenico Majone’s input into the discussion about the reform and future of the European Union. Majone voices objections to further centralization and a transfer of competences to the European level and calls for more differentiation (flexibility) of the integration process. The article discusses notions of differentiated integration and disintegration with regard to the EU and their mutual relations as well as critical arguments against the current model of European integration based on the logic of neo-functionalism. Furthermore, the concept of change in the EU is outlined – from the model based on harmonization to the one based on cooperative competition. In conclusion, weaknesses of the “club of clubs” concept are indicated together with its positive contribution to the redefinition of thinking about integration processes in Europe.